Weather and Climate Risk Communication - Guindon, Jean Bernard; Tanguay-Hebert, Flore; Motulsky, Bernard (Book collections on Project MUSE., 2017)
We are all exposed to meteorological and climate risks that impact our daily lives to some degree. A number of organizations with professionals from various areas of expertise provide solutions to prevent and manage these risks. It is critical to adequately communicate these issues to individuals who may be impacted and to the various actors involved in managing these problem situations to offset any harmful effects. The purpose of this book is to convey the role of communications in risk management. In this book, practitioners and researchers share their experiences and observations and through examples, reflections and practical exercises, they equip readers with a range of tools to improve their communications and understanding of events involving the transmission of messaging. This book deals with risk communication concepts, the actual practice of communications, communicating in a digital environment, and the overall repercussions. Readers who are either risk management and communication professionals or students are shown how they can assume an enhanced participatory role in implementing effective and relevant communications strategies that minimize the negative impact of crisis situations.